Perspectives on fixedness: applied and theoretical - Hudson, Jean (Lund Studies in English, 1998)
This thesis is about fixedness, or the process whereby orthographic words group together and congeal into fixed expressions that might subsequently reduce and become single words. The discussion focuses on three levels: realization, conceptualization, and discourse. At the level of realization, substitution tests have traditionally been employed to ascertain degrees of fixedness in expressions. This method is evaluated with respect to expressions in adverb role (complex adverbs) and found to be inappropriate. At the conceptual level, the salience of word meanings, grammatical roles, and cohesive relations signalled in expressions are examined. It appears that there is a relationship between the overall level of salience in the expressions and the extent to which they are fixed. Reinterpretation and reanalysis at the level of discourse are motivating processes in the evolution of expressions. A unidirectional, cyclical cline of language change is proposed, and its relationship to the grammaticalization cline is discussed. The eclectic approach taken in the book serves the dual function of bridging the gap between applied and theoretical approaches to linguistic research (as the title suggests), and of highlighting fixedness as an area worthy of study in its own right.
Keywords: conceptualization; grammaticalization; pragmatic inferencing; reanalysis; univerbation; English language and literature; structuration; discourse; complex adverb; salience; Engelska (språk och litteratur)